2020
DOI: 10.1186/s12912-020-00453-7
|View full text |Cite
|
Sign up to set email alerts
|

Developing a competency profile for newly graduated registered nurses in South Africa

Abstract: Background Newly graduated registered nurses experience various challenges when entering the clinical practice environment. Typical challenges include lack of specific knowledge, skills and attitude competencies which is aggravated further by factors such as transition problems, workloads, lack of confidence and independence which potentially causes poor quality care. The aim of the study was to develop a competency profile for newly graudated registered nures, based on the perceptions of both nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Here, nursing students with global visions might have the necessary capabilities to face the challenges of emerging global conditions with an awareness of shared values and belonging to a common social and cultural space [ 34 ]. Life-long learning, recognised as a necessity for the development of the nursing profession [ 35 , 36 ], is an important attitude of competency for newly graduated registered nurses [ 37 ]. With the advancement of health-related science and technology and the discovery of new diseases, we expect students to actively search for knowledge and understanding and to use these to meet their professional lifetime needs.…”
Section: Introductionmentioning
confidence: 99%
“…Here, nursing students with global visions might have the necessary capabilities to face the challenges of emerging global conditions with an awareness of shared values and belonging to a common social and cultural space [ 34 ]. Life-long learning, recognised as a necessity for the development of the nursing profession [ 35 , 36 ], is an important attitude of competency for newly graduated registered nurses [ 37 ]. With the advancement of health-related science and technology and the discovery of new diseases, we expect students to actively search for knowledge and understanding and to use these to meet their professional lifetime needs.…”
Section: Introductionmentioning
confidence: 99%
“…A competent nurse possesses these qualities and the motivation to use those in order to provide effective and quality patient care (Takase & Teraoka, 2011). It has been reported that competence is related to many difficulties experienced by newly graduated nurses during transition shock (Rabie et al, 2020).…”
Section: Holistic Nursing Competencementioning
confidence: 99%
“…Competence could be claimed as a contributor to these difficulties experienced by newly graduated nurses during the transition shock (Chen et al, 2021;Rabie et al, 2020). Responsibilities exceeding competence cause newly graduated nurses to feel inadequate, uncomfortable, unprepared and unsure while performing the job (Labrague et al, 2019;Walker et al, 2017) and fear making mistakes and harming the patient (Al Awaisi et al, 2015;Hawkins et al, 2019;Willman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…8 Enhanced education gives nurses increased confidence in not just practical skills but also interpersonal and management skills. 10 In addition, increased education empowers nurses to make changes to improve the health of patients and families and strengthen healthcare organizations and systems. 1 Some of the goals of global nursing are to increase effective nurse-led symptoms of diabetes and hypoglycemia, documentation, therapeutic communication techniques, and patient safety.…”
Section: Liberian Education Sessionsmentioning
confidence: 99%
“…Nurses need advanced clinical and critical thinking skills to manage complex care situations 8. Enhanced education gives nurses increased confidence in not just practical skills but also interpersonal and management skills 10. In addition, increased education empowers nurses to make changes to improve the health of patients and families and strengthen healthcare organizations and systems 1…”
Section: Introductionmentioning
confidence: 99%